Sind Regionalkongresse noch zeitgemäß? - Skrobek, L.; Honacker, A.; Hegele, A.; Hofmann, R. (Aktuelle Urologie, 2014)
This article poses the question whether regional meetings are still contemporary for continuing medical education using the example of this year’s joint meeting of the Vereingung der Mitteldeutschen Urologen e. V. and the Sächsischen Gesellschaft für Urologie e. V., which took place in Marburg from May 22nd – 24th , 2014. It gives an overview of the most important and interesting topics of the meeting and highlights the advantages of regional meetings in comparison to other kinds of medical education possibilities such as national conventions or internet-based courses. The authors conclude that in spite of a significant financial costs and organisational effort, regional meetings contain unique and favourable characteristics and hence should remain a permanent feature of the scientific landscape in Germany.